PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT MITRA GLOBAL HOLIDAY JIMBARAN BALI - Rena Prilian, Ni Made; Indrawati, Yayu; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 1 (2014): Jurnal IPTA (July 2014)DO - 10.24843/IPTA.2014.v02.i01.p06)
This research aim is to know the influence which is significant from work environment variable to employees performance at PT Mitra Global holiday, Jimbaran Bali. Respondents were all employees which is total amount to 52 respondents and the sampling tehnique using purposive sampling, such as sampling technique with specific consideration. Type of data used qualitative and quantitative which we derived from the premiere and secondary data. The method used to gather the information were interviews, library, research questionary and observation. The analysis technique is descriptive analysis, likert scale, correlation, determination, regression and t-test analysis. Based on the correlation analysis, its clear that the influence of the work environment on employee performance is equal to 0,804. It is mean that there’s be strong relationship influence between work environment of employees performances at PT Mitra Global Holiday Jimbaran Bali. The more conducive of work environment the better the performance of employees. Mean while, from the determination method of 64,4 percent stated that the work environment has the effect of 64.6 percent and the remaining 35,4 percent were caused by other factors. According to regretion analysis the result have t-count 9,559 > t-table 2,40 states that the influence of work environment have relation with enthusiasm of employees at PT Mitra Global Holiday, Jimbaran- Bali.
Keywords: Work Environment, Employees Performance